2012
DOI: 10.4081/pmc.2012.77
|View full text |Cite
|
Sign up to set email alerts
|

Septic arthritis in children

Abstract: Osteoarticular infections are a form of diagnostic and therapeutic emergency in infants and children, even if relatively rare. Despite decades of experience with different protocols, and multiple clinical trials, today it is still difficult to determine what kind of antibiotics is really effective, what kind of associations are required, which is the optimal time range of a treatment, when and on which subjects to base the transition from a parenteral treatment to an oral one. Current philosophy aims more and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…This difference is probably due to the delayed presentation and advanced disease in our cohort of patients. Another study by Riccio et al reported pseudoparesis in 90% patients and painful movements in 93% patients which is in concordance to our findings [8] . Twentyone cases were complicated by osteomyelitis (n=13), pathological fracture (n=3) and dislocation (n=5).…”
Section: Discussionsupporting
confidence: 93%
“…This difference is probably due to the delayed presentation and advanced disease in our cohort of patients. Another study by Riccio et al reported pseudoparesis in 90% patients and painful movements in 93% patients which is in concordance to our findings [8] . Twentyone cases were complicated by osteomyelitis (n=13), pathological fracture (n=3) and dislocation (n=5).…”
Section: Discussionsupporting
confidence: 93%